Gelatin-dopamine coating for improved biocompatibility on polydimethylsiloxane substrate surfaces - Quek, Kai Yun (2016)
The current in vitro cell culture technologies of utilizing microfluidic devices has become more common within experimental cell biology. Several decades of heuristic optimization have contributed into perfecting conventional cell culture protocols and devices. In comparison, even for polydimethylsiloxane (PDMS) being one of the most frequently used material in microfluidic cell culture devices, collective understanding of the differences in cellular behaviour between microfluidic and macroscopic culture is still progressing. Unfortunately, PDMS provides a rigid culture surface as it not favourable for cell culture and it limits the proteins adsorption on PDMS surface. This poses a major challenge in cell biology as the intrinsic high hydrophobicity property implicates incompatibility for long-term cell adhesion, proliferation and directed cell differentiation. Therefore, this study aims to customize improved biocompatible PDMS substratum by developing Gelatin-Dopamine (G-D) fabricating approach to stabilize prolonged mouse embryonic stem cell (mESCs) culture on PDMS surfaces as crosslinks coupled with proteins. G-D PDMS surface analysis revealed modification for wettability, roughness and protein attachment which improved the characteristics of PDMS that determine stem cell fates. Thus, this chemical alteration can enhance the biocompatibility of PDMS, including macro and microfluidic scaled culture systems.